The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15288/jsad.76.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alcohol Policies in Preventing Intimate Partner Violence: A Review of the Literature

Abstract: Objective-This article summarizes existing research on the relationship between alcohol policies and intimate partner violence (IPV). Because alcohol represents an important risk factor for IPV, interventions and policies aimed at decreasing problem drinking may also lead to reductions in IPV.Method-Electronic databases were searched to identify relevant peer-reviewed journal articles on alcohol policies and IPV, as well as reference sections of appropriate articles. Only policies that have been studied specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…These are important findings from a policy perspective, given that the physical availability of alcohol in the population can be directly controlled by government (e.g. reducing trading hours and number of alcohol outlets), and such policies have consistently been shown to impact on FDV and OV .…”
Section: Discussionmentioning
confidence: 87%
“…These are important findings from a policy perspective, given that the physical availability of alcohol in the population can be directly controlled by government (e.g. reducing trading hours and number of alcohol outlets), and such policies have consistently been shown to impact on FDV and OV .…”
Section: Discussionmentioning
confidence: 87%
“…The final approach under create protective environments is modifying the physical and social environment of neighborhoods (Niolon et al 2017). Research also suggests that characteristics of communities and neighborhoods are associated with higher rates of IPV, including factors such as alcohol outlet density, physical disorder and decay, social disorder, and higher rates of crime and violence (Browning 2002;Kearns et al 2015;Raghavan et al 2006). Neighborhoods with higher rates of crime and signs of disorder may impact community norms surrounding aggression and violence and decrease concerns of negative consequences for perpetration of IPV, such as police intervention (Cunradi 2010;Raghavan et al 2006).…”
Section: Strategies For Preventing Intimate Partner Violence Across Tmentioning
confidence: 99%
“…From a public health policy perspective, regulating alcohol outlets through zoning and licensing has been shown to reduce excessive alcohol consumption and related harm (Kearns et al, 2015). However, given that our limited results are the only findings so far on the subject in Denmark; further study is required to determine whether regulating alcohol outlets reduces alcohol consumption and related harm in this country.…”
Section: Menmentioning
confidence: 77%
“…With respect to alcohol-related harm, systematic literature reviews by Popova et al (2009), Campbell et al (2009), Kearns, Reidy, and Valle (2015) and Gmel, Holmes, and Studer (2016) have shown that greater alcohol availability was positively associated with alcohol-related harm. More specifically, research has shown a significant association between alcohol outlets and alcohol-related problems (Fone et al, 2016;Popova et al, 2009), assault rates (Livingston, 2008), rates of violent crime (Norstrom, 2000;Toomey et al, 2012), higher concentrations of robbery (Snowden & Freiburger, 2015), and mortality (Richardson, Hill, Mitchell, Pearce, & Shortt, 2015).…”
mentioning
confidence: 99%